Interaksionisme Simbolik Masyarakat Tradisional Dewa Tawun Dalam Memaknai Eksistensi Tradisi Keduk Beji Pada Era Modernisasi (Studi Deskriptif pada Masyarakat Desa Tawun, Kecamatan Kasreman) - Dewi, Buana Tungga (Studi Budaya Nusantara, 2022)
This study aims to obtain data about the people of Tawun Village in maintaining the Keduk Beji Tradition, Kasreman District, Ngawi. To get a clear picture of how the Tawun community carries out the Keduk Beji Tradition in the Modernization era, the research method used is descriptive with a qualitatie approach. Using data collection techniques based on the results of observations, interviews, documentation, and field notes. The data sources used are primary data sources and secondary data sources. The data analysis used is data analysis according to George Herbert Mead's Symbolic Interactionism theory with 3 concepts, namely mind, self, and sociaty. Based on the results of the research, the Tawun Village community still maintains the Keduk Beji Tradition in the Modernization Era which aims to increase solidarity with one another and appreciate the gift of nature for the life of the Tawun community and teach about caring for the environment. The ritual is held on Tuesday Kliwon every year in the month of Suro. Javanese rituals are synonymous with offerings, as is the case with Keduk Beji.